Dominasi Sosial dan Perlawanan terhadap Hegemoni Patriarki dalam Film Kartini : Kajian Hegemoni Antonio Gramsci - Dwi Ainur Rosyidah; Dewi Ananta; Bella Intan Pratiwi; Ahmad Ilzamul Hikam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the representation of patriarchal hegemony and the forms of women’s resistance in Kartini (2017), a film directed by Hanung Bramantyo, using Antonio Gramsci’s theory of hegemony as the analytical framework. The research is grounded in the persistence of patriarchal culture that places women in subordinate positions within society, including in media and film representations. The purpose of this study is to identify the forms of patriarchal domination depicted in the film and to analyze the main character’s strategies of resistance against such hegemony. The study employs a descriptive qualitative method, with data collected through observation of scenes and dialogues that reveal social domination and acts of resistance. The analysis process involves data reduction, presentation, and conclusion drawing by connecting findings with Gramsci’s theoretical concepts. The results indicate that social domination in the film is represented through restrictions on women’s education, social control, and the reinforcement of traditional values that constrain women’s roles. Patriarchy operates not through physical coercion but through social consent internalized as cultural truth. Meanwhile, Kartini’s resistance is expressed through critical awareness, education, and the dissemination of emancipatory ideas as forms of counter-hegemony. The film portrays women’s struggle to challenge patriarchal structures through intellectual strength and ideological consciousness. The findings suggest that social change begins with shifts in cultural consciousness rather than merely structural transformation.